Analisis Keruntuhan Progresif Pada Struktur Gedung Tidak Beraturan Sistem Pelat Konvensional - Apryan, Yogi Raenaldo; Djauhari, Zulfikar; Ridwan, Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Progressive collapse is the collapse caused by the collapse of an element of the structure of the building which will then affect the nearby structure resulting in a collapse either partially or completely. In the urban area the development of construction technology of the structure is now increasingly advanced, the shape building structures are not only in regular but also in irregular. The irregular of the structure would cause progressive collapse of the building. Building collapse occurs due to the burden of earthquakes, gas blasts, and collisions from airplanes. This research aimed to analysys collapse behavior of the building structures consist of a conventional plate system. Analysis was conducted according to in General Service Administration (2003). The structural strength inspection was conducted finite the element by using software. Irregular structures experienced progressive collapse when demand capacity ratio more than 1.5. The results of the analysis showed that there was an increase in the moment ratio value to the column elements and beam elements induced by the deletion of one of the column elements, in some elements the demand capacity ratio value exceeded 1.5 which was then the building collapsed. The collapse occured on the part of the elements around the elimination of columns and the type of collapse of the building was classified as an pancake-type collapse.Keywords : Progressive Collapse, Irregular Structure, Slab, Demand Capacity Ratio, General Service Administration